Effects of in vitro Culture Period of Reconstructed Embryos and Genetic Background of Feeder Cells on Establishment of Embryonic Stem Cells Derived from Somatic Cell Nuclear Transfer Blastocysts in Pigs - Na Rae Han; Song Baek; Yongjin Lee; Joohyeong Lee; Jung Im Yun; Eunsong Lee; Seung Tae Lee (The Korean Society of Animal Reproduction and Biotechnology, 2020)
The establishment of porcine embryonic stem cells (ESCs) from porcine somatic cell nuclear transfer (SCNT) blastocysts is influenced by in vitro culture day of porcine reconstructed embryo and feeder cell type. Therefore, the objective of the present study was to determine the optimal in vitro culture period for reconstructed porcine SCNT embryos and mouse embryonic fibroblast (MEF) feeder cell type for enhancing colony formation efficiency from the inner cell mass (ICM) of porcine SCNT blastocysts and their outgrowth. As the results, porcine SCNT blastocysts produced through in vitro culture of the reconstructed embryos for 8 days showed significantly increased efficiency in the formation of colonies, compared to those for 7 days. Moreover, MEF feeder cells derived from outbred ICR mice showed numerically the highest efficiency of colony formation in blastocysts produced through in vitro culture of porcine SCNT embryos for 8 days and porcine ESCs with typical ESC morphology were maintained more successfully over Passage 2 on outbred ICR mice-derived MEF feeder cells than on MEF feeder cells derived from inbred C57BL/6 and hybrid B6CBAF1 mice. Overall, the harmonization of porcine SCNT blastocysts produced through in vitro culture of the reconstructed embryos for 8 days and MEF feeder cells derived from outbred ICR mice will greatly contribute to the successful establishment of ESCs derived from porcine SCNT blastocysts.